Identifying Hemostatic Thresholds in Cancer Patients Undergoing Coronary Angiography Based on Platelet Count and Thromboelastography - Agha, Ali M.; Gill, Clarence; Balanescu, Dinu Valentin; Donisan, Teodora; Palaskas, Nicolas; Lopez-Mattei, Juan; Hassan, Saamir; Kim, Peter Y.; Charitakis, Konstantinos; Cilingiroglu, Mehmet; Oo, Thein Hlaing; Kroll, Michael; et al. (Frontiers in Cardiovascular Medicine, 2020)
Objectives: To evaluate the role of platelet count and thromboelastogram (TEG) in the treatment of thrombocytopenic cancer patients with suspected coronary artery disease (CAD). Background: Cancer patients with CAD and thrombocytopenia are often treated non-invasively due to perceived high risk of bleeding. We sought to evaluate coagulability based on TEG and determine if platelet count and TEG could predict bleeding risk/mortality among cancer patients undergoing coronary angiography (CA). Methods: Baseline demographics, platelet count, and TEG parameters were recorded among cancer patients that underwent CA and had a concomitant TEG. Logistic regression and univariate proportional hazards regression analysis were performed to determine the impact of platelet count and coagulability on 24-month overall survival (OS). Results: All patients with platelet count <20,000/mm3 and nearly all patients with platelet count 20,000-49,000/mm3 were hypocoagulable based on TEG results. In contrast, nearly all patients with platelet counts of 50,000-99,999/mm3 had normal TEG results and OS similar to those with platelet counts of ≥100,000/mm3. Coagulability based on TEG was not associated with OS. However, a platelet count of <50,000/mm3 was associated with worse 24-month OS (hazard ratio=2.76; p=0.0072) when compared with a platelet count of ≥100,000/mm3. No major bleeding complications were observed in all groups. Conclusion: The majority of cancer patients with platelet counts of <50,000/mm3 were hypocoagulable based on TEG and had worse OS at 24 months. The relatively normal TEGs in the >50,000/mm3 groups, as well as the improved survival, suggest that with appropriate clinical indication and risk/benefit assessment, a cut-off of 50,000/mm3 platelets can be considered for CA in cancer patients.